Information System Strategic Planning in IS / IT Service Provider - Hakim, Muhammad Malik (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2017)
Information System should be an enabler for the business, enabling the company to innovate, persist and evolve in trying to fulfill customer needs. This research is a case study about planning of strategic information system at one of the national IS/IT solution and product provider. Using the methodology developed by Ward and Peppard, this study investigates the urgent and necessary IS for future development and future needs, with data collected directly or indirectly in the form of primary and secondary data. Based on the results of the research, the company can develop IS which sorted by priority using Mc Farlan's Strategic Grid and grouped into support application, key operational, strategic, and high potential applications which each have different benefits of each other . Furthermore, it is expected that the development is planned to be implemented gradually in the next four years with the new IS policies that can be implemented within the company.